(untitled) (Research, Society and Development, 2025)
This study addresses the importance of preventing and controlling hypertension and diabetes mellitus (Hypertension and Diabetes Mellitus) among elderly indigenous people, highlighting the role of nursing in promoting health and strengthening self-care in the Amazonian context. The objective was to describe and propose educational strategies aimed at preventing hypertension and diabetes mellitus in elderly indigenous people. The methodology was descriptive and of a qualitative and quantitative nature, with a participatory character, including lectures, blood pressure measurements, blood glucose tests, and educational activities conducted by nursing students. The results, based on community participation, showed a high prevalence of diabetes and hypertension, especially among women, and good adherence to health education actions. It is concluded that culturally appropriate interventions strengthen primary care and contribute to the healthy aging of the indigenous population.